2019
DOI: 10.18553/jmcp.2019.25.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Patterns of Oral Disease-Modifying Drugs in Commercially Insured Patients with Multiple Sclerosis

Abstract: BACKGROUND: The approval of new oral disease-modifying drugs (DMDs), such as fingolimod, dimethyl fumarate (DMF), and teriflunamide, has considerably expanded treatment options for relapsing forms of multiple sclerosis (MS). However, data describing the use of these agents in routine clinical practice are limited. OBJECTIVE: To describe time trends and identify factors associated with oral DMD treatment initiation and switching among individuals with MS. METHODS: Using data from a large sample of commercially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Several studies have examined recent real-world treatment patterns, HCRU, and cost among patients with MS treated with DMTs [1,15,[17][18][19]. Given the speed at which the treatment landscape is evolving [20], it is important that we evaluate treatment patterns with the most current DMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined recent real-world treatment patterns, HCRU, and cost among patients with MS treated with DMTs [1,15,[17][18][19]. Given the speed at which the treatment landscape is evolving [20], it is important that we evaluate treatment patterns with the most current DMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although several real-world studies reported both oral and injectable DMAs to be tolerable, 2,8,11,12 there is mixed evidence regarding the comparative adherence of oral versus injectable DMAs. 8 Oral DMA users have shown comparable adherence relative to injectable DMAs and concluded that the route of administration of DMA was not a significant predictor of adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from 2009 to 2014, injectable DMTs were still used by 93.7% of almost 9000 individuals with MS initiating and 60.6% of those switching DMTs. 47…”
Section: Discussionmentioning
confidence: 99%